Evaluation of Microbiological Quality and Hazardous Food Additives in Elementary School Snacks in Samarinda City, Indonesia - Meli Pasiakan; Ratih Wirapuspita Wisnuwardani; Iriyani Kamaruddin; Maryam Amir (Universitas Teuku Umar, 2025)
Background/Objectives: School snacks are an important source of energy and nutrients for children, but they may pose biological and chemical safety risk if not properly controlled. This study aimed to identify the presence of Escherichia coli, salmonella and hazardous food additives, including borax, formalin, rhodamine B and methanil yellow in school snacks sold around SDN 005 Dr.Sutomo Samarinda Ulu.Design/Methods: A descriptive cross-sectional design was conducted with sampling from in three school canteens and two street vendors. A total of 12 food and beverage samples were examined at Samarinda City Regional Health Laboratory. Microbiological tests were performed using the multiple-tube fermentation method, while chemical testing were conducted using qualitative methods. Results : Laboratory analysis showed that all samples tested negative for E.coli and Salmonella. Furthermore, chemical analysis confirmed the absence of borax, formalin, rhodamine B, or methanil yellow in all samples. These findings suggest that the school snacks tested from both microbiological contamination and prohibited chemical additives.Conclusion : School snacks sold around the SDN 005 Dr.Sutomo Samarinda Ulu are relatively safe for children’s consumption. The findings also reflect the effectiveness of school and health center supervision in ensuring food safety. However, continuous monitoring and education remain essential to sustain safe food practice among students and vendors.